Analysis of Coffee MSME Production Cost Efficiency Using the Leontief Matrix Model Based on Monthly Production Data at Sumatra Roastery in Medan City - Loranty Folia Simanjuntak; Joan Unedo Siregar; Teguh Aditya Wahyudi; Paloma Elisabeth KD; Rahayu Grasela Br Aritonang; Benny sitorus (Outline Publisher, 2026)
Purpose: This study aims to examine the impact of digital technology adoption on the sales performance of culinary Micro, Small, and Medium Enterprises (MSMEs) in Medan City, particularly through the use of food delivery platforms such as Shopee Food, Go Food, and Grab Food. Methods: A quantitative approach was employed using transformation matrix modeling and Pearson correlation analysis. Data were collected through structured interviews with MSME operators who actively utilize digital platforms in their business operations. The variables analyzed include digital adoption, market reach, transaction efficiency, and consumer accessibility. Results: The findings reveal a statistically significant positive correlation between digital platform utilization and improved sales performance. Digital adoption enhances market reach by expanding customer access, increases transaction efficiency through streamlined ordering systems, and improves consumer accessibility. These factors collectively contribute to higher sales and business growth among culinary MSMEs in Medan. Originality: This study offers a novel approach by integrating transformation matrix modeling with correlation analysis to assess the impact of digitalization at the MSME level. It provides practical insights for MSME actors and policymakers in optimizing digital platforms to strengthen competitiveness in the digital economy era.